PROSPEK DAN TANTANGAN DALAM PERKEMBANGAN ASURANSI SYARIAH DI NEGARA MUSLIM - Fitriani; Hendro Lisa; Husni Thamrin; Yuslizar (Lembaga Marwah Rakyat, 2022)
The development of Islamic thought encourages the sharing of sharia-based businesses, one of which is sharia insurance. Sharia insurance has become part of the material for economic studies in general, and sharia economics in particular. This happens because along with the development of sharia insurance in Muslim countries and non-Muslim countries. This study aims to determine the prospects and challenges in the development of Islamic insurance in Muslim countries. The analytical method used is Library Research. And what is used as primary data in this study is data obtained directly from the main source, namely the literature that discusses the development of Sharia insurance in various Muslim countries. The results of this study indicate that sharia insurance has increased and the assets of sharia insurance companies have also increased, this is influenced by the growth of contributions and results of the development of existing companies' investments. The development of Islamic insurance in Muslim countries is growing rapidly and continues to experience good improvement and development, this will continue to experience continuous improvement and development.